Electrophysical сharacteristics of LEDs based on GaN epitaxial films - Oleksenko, P.Ph.; Sukach, G.A.; Smertenko, P.S.; Vlaskina, S.I.; Bogoslovskaya, A.B.; Spichak, I.O.; Shin, D.H. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
Forward and reverse current-voltage (I-V) characteristics of light emitting diodes based on GaN epitaxial films were investigated by differential spectroscopy. This technique is based on calculating the differential slope of the I-V curve in the log-log scale in the following form: α = d lg i/d lg V and γ = d lg α/d lg V. The main peculiarity of reverse I-V curves is the absence of rectification. The I(V) dependence can be approximated as i~V³ at low bias and i~V⁴ at high bias. These functions correspond to a high and superhigh level of double injection of current carriers, respectively. The forward current depends on voltage exponentially, with the ideality factor ranging from 6 to 8 under the bias of up to 1.5 V. The α(V) dependence has two maxima corresponding to a change of the charge flow mechanism from carrier diffusion to the field mechanism in the first case and to overcoming the recombination barrier in the second case. The second maximum is followed by light emission. Behavior of the I-V curves in temperature range from 150 K to 400 K is discussed and compared to that of spectral, kinetic, and power-current characteristics measured in the same temperature range. Прямі та зворотні вольт-амперні характеристики (ВАХ) світловипромінюючих діодів на основі GaN епітаксійнних плівок досліджено методом диференційної спектроскопії. Основу цього методу складає визначення диференційного нахилу кривої в подвійному логарифмічному масштабі в вигляді α = d lg i/d lg V та g = d lg α/d lg V. Основною особливістю зворотної ВАХ є відсутність випрямлення. Виявлено апроксимації ВАХ i~V³ та i~V⁴ в областях низького та високого зміщення, відповідно. Це відповідає високому та надвисокому рівням подвійної інжекції носіїв струму, відповідно. Пряма ВАХ показує експоненційну поведінку з фактором ідеальності від 6 до 8 в області зміщень до 1,5 В. Потім на залежності α(V) мають місце два максимуми, які відповідають зміненню механізму струмопроходження від дифузійного струму до польової емісії в першому випадку та подоланню рекомбінаційного бар.єру у другому. Тільки після другого максимуму починається випромінювання світла. Обговорюється поведінка ВАХ в температурному діапазоні від 150 K до 400 K. Проведено порівняння ВАХ та спектральних, кінетичних і ампер-яскравістних характеристик в тому ж температурному діапазоні. Прямые и обратные вольт-амперные характеристики (ВАХ) светоизлучающих диодов на основе GaN эпитаксиальных пленок исследованы методом дифференциальной спектроскопии. Основу этого метода составляет определение дифференциального наклона кривой в двойном логарифмическом масштабе в виде α = d lg i/d lg V и g = d lg α/d lg V. Основной особенностью обратной ВАХ является отсутствие выпрямления. Выявлены аппроксимации ВАХ i~V³ и i~V⁴ в областях низкого и высокого смещения, соответственно. Это обусловлено высоким и сверхвысоким уровнем двойной инжекции носителей тока, соответственно. Поведение прямой ВАХ показывает экспоненциальный характер с фактором идеальности от 6 до 8 в области смещений до 1,5 В. Затем на зависимости α(V) имеются два максимума, которые соответствуют изменению механизма токопрохождения от диффузионного тока к полевой эмиссии в первом случае и преодолению рекомбинационного барьера во втором. Только после второго максимума начинается излучение света. Обсуждается поведение ВАХ в температурном диапазоне от 150 K до 400 K. Проведено сравнение ВАХ с спектральными, кинетическими и ампер-яркостными характеристиками в том же температурном диапазоне.